Exfoliation of clay layers in polypropylene matrix using potassium succinate-g-polypropylene as compatibilizer - Rama, Mallikarjuna Shroff; Neppalli, Ramesh; Chellaswamy, Ramesh; Swaminathan, Sivaram (Composites Science and Technology, 2010)
The efficiency of potassium succinate-g-polypropylene (KPPSA) as compatibilizer for the dispersion of clay in a high molecular weight polypropylene during melt mixing for the preparation of nanocomposites was evaluated and compared with maleic anhydride-g-polypropylene (PPMA). Nanocomposites were prepared by direct melt mixing and by masterbatch methods and the structure obtained was characterized by WAXD and TEM. The exfoliation and better dispersion of the organoclay was observed with KPPSA than PPMA. The dispersion of clay was found to be dependent on the method of preparation, type and the amount of compatibilizer used. The dispersion was better when the nanocomposites were prepared by two step masterbatch route than the single step direct mixing method. Flexural moduli and crystallization behavior were studied and correlated with the dispersion of organoclay in the PP matrix. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: differential scanning calorimetry; Mechanical property; Nano composites; Nanoclays; polypropylene

Influence of structure of organic modifiers and polyurethane on the clay dispersion in nanocomposites via in situ polymerization - Rama, Mallikarjuna Shroff; Swaminathan, Sivaram (Journal of Applied Polymer Science, 2010)
Influence of polyurethane (PU) structure on the nature of PU/clay nanocomposite was studied using varying amounts of trimethylol propane (TMP) as branching agent. The effect of hydroxyl groups in the modifier of organoclays on the structure of PU/clay nanocomposites was studied. Nanocomposites were characterized using wide-angle X-ray diffraction measurements (WAXD) and transmission electron microscopy (TEM). The results show that formation of completely exfoliated and well dispersed polyurethane/clay nanocomposites via in situ polymerization, is facilitated by the presence of tethering groups on the clay surface and an ability to form branched and crosslinked structures. Incorporation of long alkyl chains in addition to tethering hydroxyl groups in the modifier structure of the clay did not significantly improve the compatibility of linear PU with the clay. Intercalated thermoplastic polyurethane/clay nanocomposites, prepared using poly(caprolactone diol) as soft segment and isophorone diisocyanate and 1,4-butanediol as hard segments show increase in storage tensile moduli at temperatures before glass transition temperature when functional groups capable of chemically reacting with the growing polymer chains are present in the clay modifier. This is indicative of improved interaction of the polymer with the clay surface when the modifier has larger number of hydroxyl groups. (C) 2010 Wiley Periodicals, Inc. J Appl Polym Sci 118: 1774-1786, 2010
Keywords: intercalation and exfoliation; Nanocomposites; organoclay; polyurethane